NUMERICAL AND EXPERIMENTAL INVESTIGATION OF SEMICIRCULAR SOLAR UPDRAFT TOWER SYSTEM EMPLOYING POROUS COPPER METAL FOAM - Abdul Hussein, Sarmad A.; A. Nima, Mohammed (Journal of Engineering and Sustainable Development, 2023)
The numerical and experimental study was carried out under Iraqi weather conditions to verify the improvement of the performance of the solar updraft tower system SUTS by introducing porous metal foam as a heat-absorbent plate. a semicircular basin of the solar collector was divided into two equal identical quarters. A porous foam material was fixed on one of the basins while the other basin was fixed on a traditional copper plate. The positions of the metal foam absorber plate are changed with two inclination angles (0֯ and 18֯) and the optimum position is achieved when it gives the highest thermal performance. A finite volume modeling technique is used to solve the governing equations and radiation heat transfer equations by using ANSYS Fluent. The experimental part was conducted in Baghdad / Iraq at latitude 33.3°. The presence of the metal foam absorber plate caused a significant decrease in the average temperatures of the heat-absorbent plate. The maximum airflow temperature was recorded with an inclined angle of 18◦. The metal foam as a heat-absorbent plate enhanced the efficiency and the output power of the SUTS to about 51.9% and 47.2% respectively compared to the traditional plate.